Advancing ceramic membrane technology in chemical industries applications by evaluating cost-effective materials, fabrication and surface modification methods - Maddala Sree Kanth; S. Lakshmi Sandhya Rani; Vinoth Kumar Raja (Hybrid Advances)
Ceramic membranes have gained significant research interest owing to their exceptional properties, including high thermal stability, chemical stability, biological resistance, and remarkable durability. These distinctive characteristics have positioned ceramic membranes as potential components across versatile applications, encompassing wastewater treatment, food and beverage processing, gas separation, and biomedical and pharmaceutical applications. A noteworthy focus in recent ceramic membranes research involves exploring cost-effective solutions. Numerous researchers are developing innovative ceramic membranes utilizing affordable alternative raw materials to reduce production costs. Moreover, notable attention in this area requires surface modification studies to enhance the efficiency of ceramic membranes tailored for industrial applications. This review thoroughly analyzes the recent advancements in ceramic membrane technology, encompassing an exploration of alternative cost-effective raw materials, including naturally available mineralized materials and various waste materials. In addition, various fabrication methods for ceramic membrane fabrication, such as extrusion, tape casting, slip casting, phase inversion, and powder pressing, are analyzed to achieve targeted performance specifications, offering insights into the evolving shaping methods. In addition, a comprehensive evaluation of different surface modification techniques, including dip coating, spin coating, sol-gel method, and hydrothermal method, is considered to tailor the ceramic membranes for specific applications. Finally, the concluding remarks along with the future perspectives of cost-effective ceramic membranes, focusing on cost reduction and efficiency enhancement, are presented.